Retrospective cohort study of the relationship between systolic blood pressure variability and multiple sclerosis disability. Issue 2 (17th February 2020) - Goldman, Myla D; Min, Seulgi; Lobo, Jennifer M; Sohn, Min-Woong
Abstract : Objective: To examine the relationship between visit-to-visit systolic blood pressure (SBP) variability and patient-reported outcome measure of disability in multiple sclerosis (MS) patients. Design: A retrospective cohort study of individuals with MS who completed a patient-determined disease steps (PDDS) scale between 2011 and 2015 at an MS specialty clinic. Participants: Individuals with MS for whom both a completed PDDS scale and ≥3 SBP measures within the prior 12 months of the survey were available. Main outcome measure: Participants were grouped into three classes of disability (no or mild (PDDS 0–1), moderate (2–3), severe (4–7)). SBP variability was calculated as within-subject SD using all SBP measures taken during the past 12 months. SBP variability was analysed by Tertile groups. Results: Ninety-two subjects were included in this analysis. Mean PDDS score was 2.22±1.89. Compared with subjects in Tertile 1 (lowest variability), the odds of being in a higher disability group was 3.5 times higher (OR=3.48; 95% CI: 1.08 to 11.25; p=0.037) in Tertile 2 and 5.2 times higher (OR=5.19; 95% CI: 1.53 to 17.61; p=0.008) in Tertile 3 (highest variability), independent of mean SBP, age, sex, race/ethnicity, body mass index and comorbidities (p for trend=0.008). Mean PDDS scores were 1.52±1.18 in Tertile 1, 2.73±1.02 in Tertile 2 and 2.42±0.89 in Tertile 3 after adjusting for the same covariates. Conclusions: Our results show a significant gradient relationship between SBP variability and MS-related disability. More research is needed to determine the underlying pathophysiological relationship between SBP variability and MS disability progression.